Evidence of the validity of the fairness character scale for adolescence: A Confirmatory Factor Analysis (CFA) technique - Mahfud, Ashari; Wibowo, Mungin Eddy; Mulawarman, Mulawarman; Japar, Muhammad (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2023)
The characteristic of fairness is a virtuous one that adolescents should possess as capital to interact with their social environment. However, no validity of evidence supports the score interpretation of a fairness character scale. The purpose of this study is to obtain evidence for the validity of the scale for adolescents. The research data were collected from 532 adolescents in Indonesia, ranging in age between 14 and 18 years. Scale development covers all stages of the process by assessing the required validity and reliability of evidence. Based on the ratings obtained from the scale, exploratory and confirmatory factor analysis were performed to identify the internal structure of the validity evidence. The results of the factor analysis found that the scale consisted of four factors, namely